Biosynthesis of 3,4-didehydroretinol from retinol by human skin keratinocytes in culture. - Rollman, O (1993)
The uptake and metabolism of radiolabelled retinol was studied in cultivated human skin cells. Normal epidermal keratinocytes in primary culture were able to incorporate unbound [11,12-3H]all-trans-retinol from the growth medium and transform it into 3,4-didehydroretinol (dehydroretinol) in a dose- and time-dependent manner. A total of 23% of the radioactive label became cell-associated during a 48-h incubation period when added at 7 nM to differentiated keratinocytes submerged in serum-containing, high-calcium (1.56 mM) culture medium. At that time point, 25-30% of cell-bound radioactive retinol had been converted into dehydroretinol, with no labelled retinal, dehydroretinal, retinoic acid or dehydroretinoic acid being detected in cells or medium. Thus dehydroretinol, which occurs physiologically in mammalian skin tissue in vivo, was identified as the predominant neutral retinol metabolite in cultured keratinocytes using h.p.l.c. and anhydro-derivatization procedures. At least 94% of the product, along with its precursor, was present in the cells in esterified form, with no traces of the compound being secreted into the cell environment. The rate of formation of dehydroretinol from its precursor was significantly lower in keratinocytes grown in serum-free, low-calcium (0.09 mM) culture medium, and in medium pre-incubated with excess unlabelled substrate. Furthermore, the application of 13-cis-retinoic acid (isotretinoin), a therapeutic retinoid drug known to markedly reduce dehydroretinol levels in human skin, blocked the biosynthesis of this metabolite in cultured keratinocytes. The 3,4-dehydrogenation pathway observed in this study could not be shown to operate to any significant extent in cultures of human epidermal melanocytes or dermal fibroblasts, supporting the hypothesis that keratinocytes represent the principal cell type involved in dehydroretinol formation from retinol in human skin.